Peranan Sistem Pengendalian Internal terhadap Pencegahan Terjadinya Tindakan Fraud di Pengadaan (Studi Kasus pada PT PLN (Persero) Distribusi Jawa Timur Area Malang) - Wicaksono, Satriyo Adi; Achsin, M. (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
The purpose of this study is to understand how the internal control systemÂ applied by PT PLN (Persero) Distribution of East Java Malang Area may play aÂ role in preventing the occurrence of fraud action in the procurement. During theÂ process, procurement in PT PLN (Persero) Distribution of East Java MalangÂ Area is prone against the occurrence of various acts of fraud. Therefore, we needÂ an internal control system over the procurement in PT PLN (Persero)Â Distribution of East Java Malang Area in order to prevent the occurrence ofÂ various acts of fraud itself.Â The study is conducted using the qualitative method with a descriptiveÂ research. The result of this study showed that overall, the internal control systemÂ applied is quite effective, as shown by the implementation of PLN Bersih program,Â which is able to make PLN (Persero) Distribution of East Java Malang AreaÂ become better and â€œcleanerâ€ than before. Meanwhile, in the procurementÂ process, the internal control are also have quite effective role in order toÂ preventing any kind of fraud acts. It is realized by the implementation of e-procurement program or eProc, the role of the procurement analysts, directors ofÂ job, and job inspectors, quality inspections, and implementation of OwnerÂ Estimate (OE) method.Keywords : Â Fraud, Â internal control system, procurement, Â PT PLN (Persero)Â Distribution of East Java Malang Area